Investigation of Antimicrobial Activity of the Extracts of the Leaves, Stembark and Root of Allanblackia floribunda: An Alternative Paradigm Shift Outcome. - Azuonwu Obioma; Somba, Nyenwere (Journal of Advanced Pharmaceutical Science And Technology, 2019)
Over the years, plants have been a major source of medicines, especially in the rural areas of the developing communities, with probably lack of functional health care facilities and trained health care personnel on hand for emergency medical response. However, with the dynamics and improvement in science and medicine, chemically synthesized drugs were being introduced and used to treat myriad of critical illnesses across board. Nonetheless, these were further strengthened owing to the increasing trend of drug resistance outcome, especially by the emerging and re-emerging infectious microorganisms. Thus, in the light of the above, there is a gradual but increasing steady return to the use of plants as sources of medicine and treatment of antibiotic resistance pathogens and illness across the globe. This study therefore, explores the use of antimicrobial activity of the leaves, stembark and root of Allanblackia floribunda on four bacterial isolates namely Staphylococcus aureus, Escherichia coli, Pseudomonas sp. and Bacillus sp. Methylated spirit, ethanol and distilled water were used as the extraction solvents differently. Ethanol extracts proved to be a better solvent compared with the other two while the extracts from distilled water were not active against any of the isolates. However, all the three ethanol extracts were more active against S. aureus while Pseudomonas sp. showed a higher level of resistance to the extracts. The leaves and root of the plant were more active on most of the isolates compared with the stembark as shown in the results section.
Keywords: Antimicrobials